A randomised controlled trial to assess pain with urethral swabs. Issue 2 (2nd December 2010) - Apoola, Ade; Herrero-Diaz, Maite; FitzHugh, Elley; Rajakumar, Raj; Fakis, Apostolos; Oakden, Jayne
Abstract : Background: Urethral swabs are uncomfortable due to the nature of the mucosa and may be a reason for non-attendance of men at sexually transmitted infection (STI) clinics. This randomised controlled trial describes the extent of discomfort associated with direct urethral sampling, and determines whether this varies by the type of swab used. Methods: Male patients over the age of 16 years having swab tests were invited to participate and were randomly assigned to receive either a gonorrhoea dacron-tipped swab, a chlamydia rayon-tipped swab or a plastic 10 μl urethral loop first for urethral sampling followed by the others sequentially. Discomfort was measured using a 0–100 mm visual analogue scale (VAS). Findings: 129 men having urethral swabs carried out as part of their screening tests for STI were invited to participate in the study and 121 were recruited. The median pain scores (IQR) regardless of sampling method, before and after the urethral sampling were, first 0 mm (0–0) and 50 mm (22–71) (p<0.001), second 9 mm (0–28) and 59.5 mm (38.3–78) (p<0.001) and third 10 mm (0–31) and 58 mm (29.3–80) (p<0.001). Direct urethral sampling was associated with a median pain score of 60.5 mm using a rayon swab, 52 mm using a dacron swab and 25.5 mm using a plastic loop. Interpretation: Direct urethral sampling is associated with discomfort and/or pain in men, which was significantly greater with a swab than a plastic loop. Urine should therefore be the specimen type of choice. When direct urethral sampling is indicated a loop is preferable to a urethral swab. International Standard Randomised Controlled Trial Number Register number: ISRCTN50938901.